2015
DOI: 10.3892/mmr.2015.4038
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-125a-3p effectively inhibits the cell growth and invasion of lung cancer cells by regulating the mouse double minute 2 homolog/p53 signaling pathway

Abstract: MicroRNAs (miRs) are a family of small non-coding RNAs that are 21‑24 nucleotides in length. Decreased expression of hsa‑miR‑125a‑3p is observed in a number of patients with non‑small cell lung cancer; however, it is not clear how this miRNA regulates the growth and invasion of lung tumor cells. The aim of the present study was to identify the function of hsa‑miR‑125a‑3p in the growth and invasion of lung cancer cells. The expression of hsa‑miR‑125a‑3p in the A549, NCI‑H460 and SPCA‑1 lung cancer cell lines wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…It has been shown that miR-125a-3p is downregulated and inhibits cell growth and invasion of LUAC [18][19][20][21]. In accordance, we found that miR-125a-3p expression was decreased in LUAC and associated with lymph node metastasis in patients with LUAC.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been shown that miR-125a-3p is downregulated and inhibits cell growth and invasion of LUAC [18][19][20][21]. In accordance, we found that miR-125a-3p expression was decreased in LUAC and associated with lymph node metastasis in patients with LUAC.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies show that miR-125a-3p and miR-125a-5p, downregulated in NSCLC, possess the inverse effects on migration and invasion of lung cancer cells [18], and downregulation of miR-125a-3p is associated with tumorigenesis and poor prognosis in patients with NSCLC [19]. Moreover, miR-125a-3p represses lung cancer growth and invasion by regulating the mouse double minute 2 homolog/p53 signaling [20], and NSCLC proliferation and migration by targeting metastasis-associated gene 1 [21]. miR-125a-3p is also sponged by lncRNA MALAT1 to regulate FOXM1 expression in hepatocellular carcinoma [22], and sponged by circ-MAPK4 in gliomas, circ_0012919 in systemic lupus erythematous and circLMF1 in aortic smooth muscle cells [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of positive anti-p53 antibody in IPF, irrespective of the existence of lung cancer, was as high as that in lung cancer ( 27 ). These findings suggest that the p53-signaling pathway is associated with lung cancer ( 28 30 ) and with IPF ( 31 ). Thus, we hypothesized that p53 mutation downregulation may be associated with a high incidence of lung cancer in patients with IPF.…”
Section: Discussionmentioning
confidence: 81%
“…Similar results were showed in other studies in different kinds of cancers. Overexpression of hsa-miR-125a-3p significantly inhibited the proliferation and invasion of lung cancer cells, and also is readily accessible as a diagnostic biomarker for early-stage colon cancer (CRC) [29,30]. Exosomes secreted by human adipose-derived MSCs (adMSC-Exo) can transfer miR-125a to endothelial cells and promote angiogenesis through repressing the angiogenic inhibitor delta-like 4 (DLL4) by targeting its 3′ untranslated region [31].…”
Section: Discussionmentioning
confidence: 99%